Changes in gene expression of pial vessels of the blood brain barrier during murine neurocysticercosis. - Pramod Kumar Mishra; Judy M Teale (Public Library of Science (PLoS), 2013)
In murine neurocysticercosis (NCC), caused by infection with the parasite Mesocestoides corti, the breakdown of the Blood Brain Barrier (BBB) and associated leukocyte infiltration into the CNS is dependent on the anatomical location and type of vascular bed. Prior studies of NCC show that the BBB comprised of pial vessels are most affected in comparison to the BBB associated with the vasculature of other compartments, particularly parenchymal vessels. Herein, we describe a comprehensive study to characterize infection-induced changes in the genome wide gene expression of pial vessels using laser capture microdissection microscopy (LCM) combined with microarray analyses. Of the 380 genes that were found to be affected, 285 were upregulated and 95 were downregulated. Ingenuity Pathway Analysis (IPA) software was then used to assess the biological significance of differentially expressed genes. The most significantly affected networks of genes were "inflammatory response, cell-to-cell signaling and interaction, cellular movement", "cellular movement, hematological system development and function, immune cell trafficking, and "antimicrobial response, cell-to-cell signaling and interaction embryonic development". RT-PCR analyses validated the pattern of gene expression obtained from microarray analysis. In addition, chemokines CCL5 and CCL9 were confirmed at the protein level by immunofluorescence (IF) microscopy. Our data show altered gene expression related to immune and physiological functions and collectively provide insight into changes in BBB disruption and associated leukocyte infiltration during murine NCC.